Pengaruh Pupuk Vermikompos dan NPK terhadap Pertumbuhan dan Hasil Kedelai Edamame pada Tanah Podsolik Merah Kuning - Reski, Silvanus; Susana, Rini; Ramadhan, Tris Haris (Perkebunan dan Lahan Tropika, 2024)
Edamame soybeans (Glycine max (L) Merill) are a type of soybean plant that can be consumed and can be harvested fresh. The development of soybean commodities in West Kalimantan still faces a number of challenges, one of which is low productivity. The use of soil as a planting medium for edamame soybeans is faced with various problems, including poor soil physical and chemical properties. Providing vermicompost organic fertilizer can cause the solid soil to become crumbly, increase its porosity, improve soil aeration and drainage and can cause the pores to open and soil aeration and NPP to supplement the nutrient needs that are lacking in the soil. This research aims to obtain the dose of vermicompost fertilizer, the dose of NPP and the best dose of the interaction of vermicompost fertilizer and NPP on the growth and yield of edamame soybeans on RYP soil. The research was carried out on land located in Southeast Pontianak District, Pontianak City. The research was carried out from August"“October 2023. The research used a factorial completely randomized design (CRD) consisting of 2 treatment factors. The first factor is vermicompost (p) which consists of 3 treatment levels consisting of p1 (10 tonnes/ha equivalent to 50 g/plant), p2 (15 tonnes/ha equivalent to 75 g/plant), and p3 (20 tonnes/ha equivalent 100 g/plant) and the second factor is NPP fertilizer which consists of 3 treatment levels consisting of n1 (200 kg/ha equivalent to 1.25 g/plant), n2 (300 kg/ha equivalent to 1.875 g/plant), and n3 (400 kg/ha equivalent to 2.5 g/plant). each treatment combination was replicated 3 times. The observation variables observed in the research were plant height, root volume, plant dry weight, number of production branches, number of pods and pod weight. The interaction between vermicompost treatment at a dose of 20 tons/ha and NPK fertilizer at a dose of 300 kg/ha was the best interaction dose for the variables of plant root volume, plant dry weight and number of pods per plant.